2017
DOI: 10.1002/1873-3468.12606
|View full text |Cite
|
Sign up to set email alerts
|

The microRNA miR‐124 inhibits vascular smooth muscle cell proliferation by targeting S100 calcium‐binding protein A4 (S100A4)

Abstract: S100 calcium-binding protein A4 (S100A4) induces proliferation and migration of vascular smooth muscle cells (VSMCs). We aimed to find the microRNA regulating S100A4 expression. S100A4 transcripts are abruptly increased in the acute phase of carotid arterial injury 1 day later (at day 1) but gradually decreases at days 7 and 14. Bioinformatics analysis reveals that miR-124 targets S100A4. VSMC survival is attenuated by miR-124 mimic but increased by miR-124 inhibitor. miR-124 decreases immediately after caroti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 43 publications
2
33
0
Order By: Relevance
“…These intrinsic differences are the result of adipocyte developmental origin, gene expression patterns, secretory capacity, and lipolytic activity (for review, see [27]). While traditionally AT is subdivided into WAT and BAT, there is evidence that within WAT depots, there is heterogeneity.…”
Section: Discussionmentioning
confidence: 99%
“…These intrinsic differences are the result of adipocyte developmental origin, gene expression patterns, secretory capacity, and lipolytic activity (for review, see [27]). While traditionally AT is subdivided into WAT and BAT, there is evidence that within WAT depots, there is heterogeneity.…”
Section: Discussionmentioning
confidence: 99%
“…Until now, only about a dozen microRNAs had been shown to be involved in vascular calcification ( 94 95 ). Our group found that miR-124 inhibits the proliferation of VSMCs by targeting S100 calcium-binding protein A4 (S100A4), which has an important role in the proliferation of VSMCs and correlates with mineralization ( 96 97 ). In addition, our computational prediction suggests that MDM2 could also be a potential target of miR-18a.…”
Section: An Alternative Epigenetic Regulation Of Vascular Calcificatimentioning
confidence: 99%
“…The microRNA expression profile in rat vessels was first described by Ji et al 12 ) , and the microRNA expression profile of human PAD was originally described in our previous study 13 15 ) . The cellular tropism of microRNA expression and function demonstrates that it could be an ideal potential therapeutic target for ISR 5 , 6 , 16 ) . However, direct evidence as to whether microRNAs are involved in the process of ISR in human arteries with PAD is still missing 16 ) .…”
Section: Introductionmentioning
confidence: 99%